Estudo biográfico sobre políticas de transferência de renda condicionada no Brasil : atender necessidades para desenvolver capacidades - Rinaldi, Débora (2022)
This study analyzes the role of the Bolsa Familia Program (PBF) in the lives of beneficiaries, residents of the city of Porto Alegre, users of one of the 22 Reference Centers for Social Assistance (Cras) operating in the municipality. Based on an interpretative research methodology, I analyze the beneficiaries' experiences with the PBF based on the following question: considering their biographical experiences as a whole, what is the role that the cash transfer program is shown to play in their lives? In total, ten narrative biographical interviews were conducted with men and women who were benefit holders. Of these, three interviews were reconstructed using the biographical case reconstruction method, whose results were synthesized into three different types of roles or functions played by the program. As a complement to the family income, acquired in the informal labor market, the benefit did not allow in any of the three cases the overcoming of food insecurity and with-it extreme poverty, which were only achieved after the (re)placement of beneficiaries in the formal labor market. On the other hand, its receipt, as well as access to the other services of the social assistance network, stood out as having functioned as a way to compensate insecure social ties, despite all its limits in fulfilling this role. Moreover, the results indicate that, in some circumstances, the program has enabled the development of new capabilities on the part of beneficiaries. If, as a policy of ends, the program was not able to provide social protection in the cases analyzed, as a policy of means it was more effective, working as a channel to bring the interviewees closer to the social welfare network, as well as to foster and develop capabilities.